(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Thyroid cancer is a heterogeneous malignancy characterized by distinct molecular and genetic alterations that influence tumor initiation, progression, and clinical behavior. Advances in genomic and transcriptomic profiling have identified recurrent mutations and rearrangements, including BRAF V600E, RAS, RET/PTC, and TP53, which play crucial roles in tumor proliferation, differentiation, and metastatic potential. These molecular changes are closely associated with histopathological subtypes, guiding risk stratification, prognostic assessment, and therapeutic decision-making. Clinical manifestations of thyroid cancer, such as tumor size, lymph node involvement, and aggressiveness, often correlate with underlying genetic profiles. Comprehensive understanding of molecular and genetic mechanisms has facilitated the development of targeted therapies, including kinase inhibitors and precision medicine approaches, improving patient outcomes. This review summarizes current knowledge on molecular, genetic, and clinical alterations in thyroid cancer and highlights their implications for diagnosis, prognostication, and individualized treatment strategies.